Environmental reporting practices of Malaysian Government Linked Companies (GLCs) - Mokhtar, Norsyahida; Sulaiman, Maliah (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
The main objective of the study is to examine the extent Malaysian government-linked companies (GLCs) report on the environment. The government has strongly emphasised social and environmental responsibility amongst GLCs through the introduction of the 'Silver Book' and other "green" initiatives. Given this and the fact that GLCs are affiliated to the government and clearly "visible", the primary concern is their "accountability" to the people. More importantly, the extent these GLCs promote sustainable development and accord with the government's vision is indeed a topic worthy of study. The results show that albeit the "visibility" and "accountability" aspects attached to GLCs, the level of environmental disclosure was rather low. Additionally, almost 30 percent of the companies did not report on the environment. In the matched-pair analysis (matching with the non-GLCs), the study found that there is no statistical difference in the level of environmental disclosure of GLCs and non-GLCs in environmentally sensitive industries. Further, the study found no significant difference in the level of environmental disclosure between GLCs in environmentally sensitive industries and less sensitive industries. The nature of the disclosure was also consistent between both categories of industries where most of the environmental information disclosed was in the declarative form.